2016
DOI: 10.1515/ijdhd-2015-0023
|View full text |Cite
|
Sign up to set email alerts
|

Technology to support positive occupational engagement and communication in persons with multiple disabilities

Abstract: Persons with multiple (intellectual and sensory-motor) disabilities can have serious difficulties managing their independent engagement in leisure activities and communication, particularly with partners not present in their immediate environment.This study assessed two versions of a technology-aided program (involving a computer system to present leisure and communication options and a microswitch to choose among them) with four participants with multiple disabilities. Two participants used the first version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…One common trait of many people with intellectual and other disabilities, neurodegenerative diseases, and acquired brain injury is the inability to engage in leisure activities independently (23, 37, 64, 65). This apparent inability may be largely due to difficulties in reaching and operating devices typically used to access leisure activities (e.g., television, computer, and music instruments).…”
Section: Support Tools To Promote Leisure Communication or Bothmentioning
confidence: 99%
See 2 more Smart Citations
“…One common trait of many people with intellectual and other disabilities, neurodegenerative diseases, and acquired brain injury is the inability to engage in leisure activities independently (23, 37, 64, 65). This apparent inability may be largely due to difficulties in reaching and operating devices typically used to access leisure activities (e.g., television, computer, and music instruments).…”
Section: Support Tools To Promote Leisure Communication or Bothmentioning
confidence: 99%
“…These problems may be characterized by the people's inability to (a) express their requests for caregivers and staff's attention or make other types of requests, and/or (b) reach relevant partners (e.g., preferred family or staff members) not immediately available in their context. The aforementioned problems may be related to lack of speech and alternative communication options and/or inability to use telephones or other devices to interact with distant partners (2, 37, 7072). Studies have typically addressed one of the problems (i.e., either the leisure or the communication problem) at a time (1, 24, 29, 37, 73, 74).…”
Section: Support Tools To Promote Leisure Communication or Bothmentioning
confidence: 99%
See 1 more Smart Citation
“…3.6.3. Easier (13) Many reported that their AT had made things (tasks/life) easier for them with numerous comments beginning with: It has made it much easier . .…”
Section: Can Go Out With My Grandson-just the Two Of Us [Using A Mmentioning
confidence: 99%
“…[family member/carer of a person using a vehicle hoist] 3.6.4. Independence (13) Being able to undertake activities without the assistance of others was also a highly valued outcome of AT.…”
Section: Can Go Out With My Grandson-just the Two Of Us [Using A Mmentioning
confidence: 99%